Effects of Computer-Assisted Instruction (CAI) on Students’ Achievement and Interest in Secondary School Physics in Jos North Local Government Area of Plateau State, Nigeria. - Usman, Isa Shehu; Jilang, Warangji Wartung (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
The study investigated the Effects of Computer–assisted Instruction, (CAI) on Students’ achievement and interest in Secondary School Physics in Jos North Local Government Area, Plateau State. This study was motivated because of the prevalence of poor students’ performance in physics which was due to defective method of teaching used by teachers. The design used in this study was quasi-experimental design. Specifically the pretest posttest control group design. The sample of the study comprised of eighty five (85) SS2 physics students in Jos north local government area of plateau state Nigeria. Three research questions and four hypotheses were formulated to guide the study. Two instruments namely physics achievement test (PAT) and physics interest questionnaire (PIQ) were used to collected data for the study. The PAT consisted of 40-items which is developed based on the concept of units and measurements, motion, vectors, projectile and simple harmonic motion while PIQ consisted of 16-items. The two instruments were validated by two experts a Prof. of physics education from the department of science and technology education university of Jos and a senior lecturer from Test and Measurement Unit in the Department of Educational Foundation all in the University of Jos. The reliabilities of the two instruments PAT and PIQ was computed and the indexes stood at 0.85 and 0.88 respectively. Data collected for the study were analyzed with the used of simple percentages, t-test and analysis of variance (ANOVA) using SPSS version 22. The findings of the study revealed that the use of CAI helped in enhancing students’ achievement in physics, helped in improving students interest in physics. The findings also showed that conventional lecture method does not help in enhancing students’ achievement in physics. The results of the hypotheses tested revealed that there was significant difference between the mean achievement scores of posttest and the mean achievement scores of pretest of experimental group, There was no significant difference between the pre-test and posttest physics achievement mean scores of students in control and the experimental groups, There was no significant difference between the post-test achievement mean scores of the experimental group and There was no significant difference between the pretest and posttest physics achievement scores of male and female in the experimental group. The study then recommended among others that workshops should be organized for physics teachers so as to educate them on the use of computer assisted instruction. These workshops should be held periodically for freshly recruited teachers. Keywords: Physics, Computer-Assisted Instruction, Achievement and Interest.